Social Studies Pre-service Teachers’ Awareness of Solid Waste and Recycling - Karatekin, Kadir (Elsevier BV, 2014)
AbstractThe purpose of this study is to determine the social studies pre-service teachers’ awareness of solid waste and recycling. A form, including 7 open-ended questions, was prepared by the researcher for this purpose in order to present pre-service teachers’ awareness of solid waste and recycling. The research was conducted within qualitative perspective as a special case study. Data for the study were collected from 165 pre-service teachers who attend classes in 1st, 2nd, 3rd, and 4th year at Social Studies Department, College of Education, Kastamonu University. The research concluded that social studies pre-service teachers have low levels of knowledge and awareness of solid waste and recycling.
Keywords: social studies pre-service teachers; solid waste; recycling; Social studies; and awareness; 2. Zero hunger; 4. Education; 12. Responsible consumption